The role of periostin as an inflammatory marker in bronchial asthma in children - N. A. Belykh; I. V. Pisnyur; A. A. Nikiforov; L. V. Nikiforova (Аллергология и Иммунология в Педиатрии, 2024)
Introduction. The extracellular matrix protein periostin, expressed in a number of body tissues, is considered as a marker of type 2 T cell inflammation and of asthma control.Objective. To study the relationship the serum periostin concentration in blood serum depending on the severity of asthma and indicators of respiratory function in children.Materials and methods. The cross-sectional (simultaneous) study included 80 children aged 6 to 17 years (average age 12±3.2), who were divided into 2 groups: 1st — children with asthma (n=40); 2nd — comparison group (n=40). The concentration of periostin in the blood serum was determined by the ELISA method. The spirographic study was performed on a computer spirometer Spirolab 1, MIR (Italy).Results. The Me of periostin in group 1 was within the normal range (730.2 ng/ml), but statistically significantly exceeded the indicator of group 2 (539.7 ng/ml, p<0.05) and did not depend on the age, duration and severity of asthma, anthropometric parameters of the examined. The level of periostin in the blood serum significantly correlated with the frequency of exacerbations of the disease during the year (r=0.74, p=0.000), with the status of asthma control (r=0.32, p=0.04). A moderate correlation was found between the level of periostin and FEV1 (r=−0.34; p=0.03).Conclusions. In children with asthma, the median periostin in the blood serum increased in proportion to the severity of asthma, disease control and the frequency of exacerbation of the disease.